Evaluation of the Epidemiological Surveillance Program at Community Health Centers in Preventing Extraordinary Events (KLB) - Nurul Aisyiyah Puspitarini; Djunaedi Djunaedi; Nurhasanah Syaharuddin; Andi Kamal M. Sallo (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Surveillance plays a crucial role in the early warning system for infectious diseases and outbreaks. Community health centers, as the spearhead of primary health care, have the primary responsibility for implementing continuous surveillance activities. This study aims to evaluate the implementation of epidemiological surveillance programs at community health centers in preventing outbreaks and to identify supporting and inhibiting factors. The research method used a descriptive evaluative approach with the CIPP (Context, Input, Process, Product) model. Data were collected through in-depth interviews with surveillance officers, direct observation of reporting activities, and review of weekly infectious disease report documents. The research results show that from a contextual perspective, policies and implementation guidelines are available but have not been consistently implemented. From an input perspective, limited human resources and reporting facilities are the main obstacles. From a process perspective, routine data collection and reporting activities are ongoing, but timeliness and analysis of disease trends are still suboptimal. Meanwhile, from a product perspective, the surveillance system has assisted in the early detection of several potential outbreaks, although it has not been optimal in comprehensive prevention. In conclusion, the epidemiological surveillance program at the Community Health Center has been running according to guidelines but requires strengthening the capacity of surveillance personnel, increasing the use of information technology, and more effective cross-sector coordination.